a^3 -27 = (a-3) (a^2+3a +9). ; U^3 +8 = (U+2) ( U^2 -2U +U^2 1-P^3 = (1-P) ( 1+P +P^2)

4 - T^2 = ( 2+T) (2-T) ; 8 m^3 +27 =. (2m+3) ( 4m^2 - 6m +9).

x^3 -8y^3 = (x-2y) ( x^2 +2xy +y^2) : b^3 -125 = (b-5) (b^2 +5b+b^2); K^2 - 36 = (K+6) (k-6)

x^3 + 343y^3 = (x+7) ( x^2 - 7x +49) 125 x^3 -216 = (5x-6) ( 25x^2 +30x+36)

125-27a^3 = (5-3a) (25+15a +9a^2). m^2-49 = (m+7) ( m-7)

x^3 +125 = (x+5) (x^2 -5x + 25). 8y^3 +1 = (2y+1) ( 4y^2-2y +1). 64x^3 +1 = (4x+1) ( 16x^2-4x+1)

125-x^3 = ( 5-x) ( 25 + 5x+ x^2). y^-4 = (. y+2) (y-2)

I have answered your question.

Niru

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up